Students’ Motivation and Expectation in Joining English Education Department at IAIN Kudus - Suciati Suciati; Nurul Aini Rizqina; Annas Mukhlisuddin (Universitas Dian Nuswantoro, 2019)
Abstract. English Education Department at IAIN Kudus is new study program. Nevertheless, the number of the students is always increased every year. This study aims to get information related to the educational background of students, analyze their motivation and expectation in joining English Education Department IAIN Kudus and analyze their ways in realizing the expectations. This study was descriptive qualitative research. It was conducted at English Education Department, IAIN Kudus. The subjects were 204 students from the first to third academic year. Data were collected through questionnaire, interview and document analysis. The results showed that 20,6% are boys and 79,4% are girls. 44, 6% of the students graduated from science program, 26 % from social program, 12,3 % from language program and the rest were from religion, computer and network engineering, sharia banking, accountancy and administration. They take and study English because of internal and external motivation. The internal factors are needs, plan, pleasure and meaning. And the external factors are learning environment, career, society and others. For the expectation, they expect to have class with clear curriculum, Students Centered Learning (SCL) and teaching media that meets their needs so they are able to develop English skills and be good English teacher/educator. And the students’ ways in realizing their expectations are studying hard, critical thinking, using appropriate media and having partner.Keywords: educational background, students’ motivation and expectation, ways Abstrak. Tadris Bahasa Inggris di IAIN Kudus adalah program studi baru. Namun, jumlah mahasiswa selalu bertambah setiap tahun. Penelitian ini bertujuan untuk mendapatkan informasi terkait latar belakang pendidikan siswa, menganalisis motivasi dan harapan mereka untuk bergabung dengan Tadris Bahasa Inggris IAIN Kudus dan menganalisis cara mereka dalam mewujudkan harapan mereka. Penelitian ini adalah penelitian deskriptif kualitatif di Tadris Pendidikan Bahasa Inggris IAIN Kudus. Responden sejumlah 204 mahasiswa dari tahun akademik pertama hingga ketiga. Data dikumpulkan melalui kuesioner, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa 20,6% adalah laki-laki dan 79,4% adalah perempuan. 44, 6% dari mereka lulus dari program sains, 26% dari program sosial, 12,3% dari program bahasa dan sisanya dari agama, teknik komputer dan jaringan, perbankan syariah, akuntansi dan administrasi. Mereka kuliah di TBI IAIN Kudus karena adanya motivasi internal dan eksternal. Faktor internal adalah kebutuhan, rencana, minat dan makna. Dan faktor eksternal adalah lingkungan belajar, karier, masyarakat dan lain-lain. Mereka berharap memiliki kurikulum yang jelas, Student Centered Learning (SCL) dan media pengajaran yang memenuhi kebutuhan mereka sehingga mereka dapat mengembangkan keterampilan bahasa Inggris dan menjadi guru / pendidik bahasa Inggris yang baik. Cara mahasiswa dalam mewujudkan harapan mereka adalah dengan belajar keras, berpikir kritis, menggunakan media yang tepat dan memiliki partner belajar.Kata kunci: latar belakang pendidikan, motivasi dan harapan siswa, cara